Approaches Reflected in Academic Writing MOOCs - Kwak, Subeom (International Review of Research in Open and Distributed Learning, 2017)
Since it was first introduced in 2008, Massive Open Online Courses (MOOCs) have been attracting a lot of interest. Since then, MOOCs have emerged as powerful platforms for teaching and learning academic writing. However, there has been no detailed investigation of academic writing MOOCs. As a result, much uncertainty still exists about the differences of writing MOOCs compared with traditional types of writing instruction in the classroom. Drawing on historical emphases in writing instruction, five approaches are illustrated: skills, creative writing, process, social practice, and a socio-cultural perspective. This study uses data from six academic writing MOOCs to examine what approaches are revealed within their writing instructions. Focusing on a group of six academic writing MOOCs at college level, attributes and features of writing MOOCs were explored by analyzing syllabi, video lectures, and assignments. Overall, the study found that these academic writing MOOCs stick to a traditional model of teaching writing, “writing as skills.” These findings suggest that instructors who teach academic writing through online platforms showed that their immediate concerns were not a social practice or socio-cultural context. Rather, teaching and learning of grammatical accuracy and surface features of texts at college level appear to be best purpose of academic writing MOOCs.